Evaluating Southeast Sulawesi’s Department of Human Resource Development Apparatus’ Education and Training Programs - Malesa Malesa (International Journal Labs, 2021)
This study aims to find information about the implementation of the Education and Training (Diklat) program at the Human Resources Development Agency (BPSDM) of Southeast Sulawesi Province. This study uses the Discrepancy Evaluation Model (DEM). This study uses a qualitative method with a population of social situations at the Human Resources Development Agency of Southeast Sulawesi Province, Regency and City with a sample of 24 informants from the province and 60 regencies and cities. The data analysis results show that: 1) the quality of the implementation of education and training programs for the apparatus is in accordance with the implementation of tasks that have been required by the institution; 2) the results of performance achievements show various responses from each informant; 3) the implementation of the Education and Training program at the Provincial BPSDM has reached the standard, while the Regency and City have not yet reached the standard; 4) Influential factors in the implementation of the education and training program are supported through the provision of infrastructure, widyaiswara/resources/trainers, methods, evaluation and follow-up. The findings recommend that institutions need to provide the necessary infrastructure, allocate APBD funds, competency-based curriculum, and post-training alumni follow-up activities.